Cirolana bambang, a distinctive new species of Cirolana Leach, 1818 (Crustacea: Isopoda: Cirolanidae) from Bitung, Indonesia - Sidabalok, Conni M.; Bruce, Niel L. (Zootaxa, 2018)
Cirolana bambang sp. nov. from Bitung, North Sulawesi, Indonesia is described. The species can be recognised by generally smooth body with small, acute, submedian nodules on pleonites 4–5 and the anterior dorsal surface of the pleotelson together with a flat, pentagonal frontal lamina, linguiform and sexually dimorphic pleotelson with the dorsal surface covered by short setae in males, deeply bifid uropod apices, and a conspicuously large robust seta on the superodistal angle of pereopod 1 ischium. Cirolana bambang sp. nov. appears to belong to a group of Indo-West Pacific Cirolana with prominent penial process, a large robust seta on the superodistal angle of pereopod 1 ischium and the presence of setae on dorsal surface of pleotelson and or uropod in males. The most similar species are Cirolana comata Keable, 2001; Cirolana dissimilis Keable, 2001; Cirolana aldabrensis Schotte & Kensley, 2005; and Cirolana somalia Schotte & Kensley, 2005. Cirolana kiliani Müller, 1993 and C. somalia are found not to belong to the Cirolana‘parva-group’.